EWMA chart with curtailment for monitoring fraction nonconforming. Issue 4 (2nd October 2017) - Haridy, Salah; Rahim, M. Abdur; Selim, Shokri Z.; Wu, Zhang; Benneyan, James C.
Abstract: The binomial Exponentially Weighted Moving Average (EWMA) control chart has been widely used as an effective tool for detecting small and moderate shifts in fraction nonconforming ( p ). This article presents a binomial EWMA chart employing a curtailment technique (abridged as Curt_EWMA chart) for monitoring p . The p shift is assumed to follow a Rayleigh distribution. It is found that the curtailment technique can improve the overall detection speed of the EWMA chart while maintaining the false alarm rate at a specified level. An algorithm is presented to find the optimal design of the Curt_EWMA chart. The results of the comparative study reveal that the Curt_EWMA chart outperforms the EWMA chart without curtailment by 41%, in terms of the average number of defectives, under different settings.